Powassan Virus in Mammals, Alaska and New Mexico, USA, and Russia, 2004–2007 - Deardorff, Eleanor R.; Nofchissey, Robert A.; Cook, Joseph A.; Hope, Andrew G.; Tsvetkova, Albina; Talbot, Sandra L.; Ebel, Gregory D.
Powassan virus is endemic to the United States, Canada, and the Russian Far East. We report serologic evidence of circulation of this virus in Alaska, New Mexico, and Siberia. These data support further studies of viral ecology in rapidly changing Arctic environments.